An embedded 1149.4 extension to support mixed-signal debugging - José Martins Ferreira (2011)
Debugging electronic circuits is traditionally done with bench equipment directly connected to thecircuit under debug. In the digital domain, the difficulties associated with the direct physical access tocircuit nodes led to the inclusion of resources providing support to that activity, first at the printedcircuit level, and then at the integrated circuit level. The experience acquired with those solutions led tothe emergence of dedicated infrastructures for debugging cores at the system-on-chip level. However,all these developments had a small impact in the analog and mixed-signal domain, where debuggingstill depends, to a large extent, on direct physical access to circuit nodes. As a consequence, when analogand mixed-signal circuits are integrated as cores inside a system-on-chip, the difficulties associatedwith debugging increase, which cause the time-to-market and the prototype verification costs to alsoincrease.The present work considers the IEEE1149.4 infrastructure as a means to support the debugging ofmixed-signal circuits, namely to access the circuit nodes and also an embedded debug mechanismnamed mixed-signal condition detector, necessary for watch-/breakpoints and real-time analysisoperations. One of the main advantages associated with the proposed solution is the seamlessmigration to the system-on-chip level, as the access is done through electronic means, thus easingdebugging operations at different hierarchical levels.